Hand grip strength as a nutritional marker in pd and hemodialysis patients - Yuvaram N.V. Reddy; Laskmi Revathi S; Thiyagaraja Thandavan; T Jayaseelan; Milly Mathew; Georgi Abraham (The Korean Society of Nephrology, 2012)
This is a prospective study evaluating hand grip strength as a nutritional marker in maintenance dialysis patients. Thirty CAPD and 50 MHD patients were assessed for hand grip strength (in the non-fistula arm) and demographic variables. In the MHD, 60% diabetic and in PD 66.7% were diabetic. In the MHD patients, Mean Age - 53.62±12.45, 78% Males and 22% Females, Hb-9.7±1.1 g/dL and 3.86±2.83 years on dialysis and in PD patients, mean age - 58.6±11.52 , 63.3% males and 26.7% females, Hb - 10.5±1.4 g/dL and 3.33±2.6 mean years on dialysis. Hand Grip Strength was 11.58+3.7 kg pre-dialysis and 9.2+3.6 kg post dialysis in MHD and 10.8+2.9 kg in PD patients. We found that malnutrition was present in 90% of MHD (10% severe, 24% moderate, 56% mild) and 100% (6.7% severe, 40% moderate, 53.3% mild) of PD patients via hand grip comparison. In conclusion, hand grip strength is a simple tool to measure the muscle mass as a measure of malnutrition in dialysis patients.